Anding-andingen in The Perspective of Systemic Functional Linguistics - Gintings, Immanuel Prasetya; Sinar, Tengku Silvana; Saragih, Amrin (Jurnal Ilmiah Peuradeun, 2018)
Systemic Functional Linguistics (SFL) concerns three metafunction meanings: clause as message, clause as exchange, and clause as representation. This article tries to analyze anding-andingen, one of oral tradition in Karo culture. The points of this paper are only two kinds of metafunctions could be applied to anding-andingen: clause as message and clause as representation. The clause of exchange could not be applied to anding-andingen since anding-andingen is an Adjunct form so it does not have the potential to be Subject; Therefore, it cannot be upgraded to an interpersonal status of capital responsibility. Anding-andingen form cannot be categorized as a clause because at the semantic level, although its form resembles a clause, but is used to describe a person's nature or condition. In using anding-andingen, if the clause is preceded by a nominal group of Subject and followed by anding-andingen as a prepositional phrase or adverbial group, the textual function will be Rheme, but if the clause begins with anding-andingen, it will be Marked Theme.